The prevalence and genetic disorders spectrum of thalassemia among breast cancer patients in Jiangxi province, China - Ding, Jingxian; Huang, Zhaohui; Jiang, Xiaoliu; Li, Qingge; Cao, Yali; Guo, Yonghong (Frontiers in Genetics, 2022)
Background: Thalassemia is a common inherited hematological disease with genetic disorders characterized by imbalanced synthesis of the globin chains. Due to the improvement of treatment methods, patients with thalassemia can survive for a long time. Therefore, it is not uncommon for patients with thalassemia suffering from malignant tumors. However, there are quite few reports on thalassemia patients complicated with breast cancer. Herein, we try to investigate the prevalence and genetic disorders spectrum of thalassemia in patients with breast cancer. Methods: Blood routing tests and serum ferritin analysis were conducted in 1887 breast cancer patients treated in the department of radiation oncology during 1 April 2020 and 30 March 2022. The suspected thalassemia carriers with small mean corpuscular volume (MCV), mean corpuscular hemoglobin content (MCH) or mean corpuscular hemoglobin concentration (MCHC) but the concentration of serum ferritin within normal limits were further investigated by polymerase chain reaction (PCR) and flow through hybridization gene chip to detect common mutations of α-globin and β-globin genes using Thalassemia Geno Array Diagnostic Kit. The prevalence and genetic mutation spectrum of thalassemia among breast cancer patients were analyzed. Results: Four hundred and eighty-nine suspected thalassemia carriers were detected by complete blood cell counts and serum ferritin analysis among 1887 breast cancer patients. One hundred and seven cases (5.7%) were identified as carriers of thalassemia, of which 55 cases (51.4%) were α-thalassemia, 50 cases (46.7%) were β-thalassemia, and 2 cases (1.9%) were co-inheritance of α-thalassemia and β-thalassemia simultaneously. In α-thalassemia, the most prevalent genotype is -SEA/αα; as for β-thalassemia, βIVS−II−654/β is the most common genotype. The degree of anemia is more severe in β-thalassemia than in α-thalassemia. Conclusion: This is the first comprehensive molecular epidemiological investigation on thalassemia among breast cancer patients. Our data indicated that thalassemia was not uncommon in breast cancer patients. The physicians should have the knowledge to avoid misdiagnosis as iron deficiency anemia.